The physiology of cross country skiing
- Fiber type composition - Movement speed on skis - VO2 max in elite skiers - What is limiting maximal oxygen consumption? - Are the skiers of today better than in the past? - The upper body in skiing - Muscle strength - Race day - Economy and skiing technique(s)